Integrated strain engineering and bioprocessing strategies for high-level bio-based production of 3-hydroxyvalerate in Escherichia coli - D. Miscevic; J.-Y. Mao; D. Abedi; C.-C. Huang; M. Moo-Young; C. P. Chou (Applied Microbiology and Biotechnology, 2020)
As petro-based production generates numerous environmental impacts and their associated technological concerns, bio-based production has been well recognized these days as a modern alternative to manufacture chemical products in a more renewable, environmentally friendly, and sustainable manner. Herein, we report the development of a microbial bioprocess for high-level and potentially economical production of 3-hydroxyvalerate (3-HV), a valuable special chemical with multiple applications in chemical, biopolymer, and pharmaceutical industries, from glycerol, which can be cheaply and renewably refined as a byproduct from biodiesel production. We used our recently derived 3-HV-producing Escherichia coli strains for bioreactor characterization under various culture conditions. In the parental strain, 3-HV biosynthesis was limited by the intracellular availability of propionyl-CoA, whose formation was favored by anaerobic conditions, which often compromised cell growth. With appropriate strain engineering, we demonstrated that 3-HV can be effectively produced under both microaerobic (close to anaerobic) and aerobic conditions, which determine the direction of dissimilated carbon flux toward the succinate node in the tricarboxylic acid (TCA) cycle. We first used the ∆sdhA single mutant strain, in which the dissimilated carbon flux was primarily directed to the Sleeping beauty mutase (Sbm) pathway (via the reductive TCA branch, with enhanced cell growth under microaerobic conditions, achieving 3.08 g l-1 3-HV in a fed-batch culture. In addition, we used the ∆sdhA-∆iclR double mutant strain, in which the dissimilated carbon flux was directed from the TCA cycle to the Sbm pathway via the deregulated glyoxylate shunt, for cultivation under rather aerobic conditions. In addition to demonstrating effective cell growth, this strain has shown impressive 3-HV biosynthesis (up to 10.6 g l-1), equivalent to an overall yield of 18.8% based on consumed glycerol, in aerobic fed-batch culture. This study not only represents one of the most effective bio-based production of 3-HV from structurally unrelated carbons to date, but also highlights the importance of integrated strain engineering and bioprocessing strategies to enhance bio-based production.